(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Denture materials must have robust mechanical properties to withstand high pressures within the mouth. The present study investigates the mechanical properties, including the tensile, hardness, and impact of a new denture composite made of poly(methyl methacrylate) (PMMA) and reinforced with eggshell (ES) powder. The new PMMA (PMMA-EC) was manufactured by mixing different ratios of ES (1 to 7% wt.) with 5% (wt) of Chitosan (CS) (as antibacterial). The new composite was tested for the tensile, hardness, and impact, and the results were compared with those of the traditional PMMA-EC (containing only 5% chitosan). Additionally, a Scanning Electron Microscopy (SEM) was used to examine the dispersion of ES in the material. The results of this study indicated that adding 1% of ES powder did not affect the mechanical properties of the composite. However, increasing the ratio of ES powder to 5% achieved the best improvement in the mechanical properties of the new composite, while increasing the ES ratio by more than 5% caused a considerable decrease in the mechanical strength. Generally, the tensile, hardness, and impact of the new denture composite were examned, respectively